Oxi-P GUI: A Graphical User Interface (GUI) for wastewater treatment process in oxidation pond - Mohd Fauzi, Syafiqah Hanis; Mohd Jamil, Norazaliza (Penerbit UMP, 2022)
The wastewater treatment process is aimed to reduce pollution to the appropriate level. An oxidation pond system can treat contaminants in wastewater. Oxidation ponds are use sunlight, bacteria, and algae to treat wastewater. This study developed an improved mathematical model and a graphical user interface (GUI), called oxi-P GUI to predict the wastewater treatment process in an oxidation pond. The correlation between dissolved oxygen (DO), chemical oxygen demand (COD), coliform bacteria, as well as concentrations of phototrophic bacteria (PSB) were examined. In MATLAB software, a revised model consisting of ordinary differential equations (ODEs) set of integrating the Monod equation was numerically solved utilising the fourth order Runge-Kutta method. The current model's root mean square error (RMSE) values were compared to the suggested model's RMSE values for model validation. The model offered a more accurate estimate than the existing model of changes in the amount of concentration in oxidation pond, which was necessary to produce acceptable water quality. A wastewater management personnel may use GUI to track water quality and determine the most effective wastewater treatment mechanism. Additionally, this user-friendly GUI will give a better understanding about the treatment process, especially to people with less programming skills.